Analisis Nilai Moral Novel Dilan (Dia adalah Dilanku Tahun 1990) Karya Pidi Baiq - Aryanti Agustina; Inawati Inawati; Haryadi Haryadi (Bastrando: Jurnal Bahasa dan Sastra Indonesia, 2023)
The purpose of this research is to describe the moral values ​​contained in the Novel Dilan (He Is My Dilan 1990) by Pidi Baiq. The method used is descriptive method. Data collection techniques using documentation techniques and note-taking techniques. Based on the results of the research, it was found that the novel has moral values, namely: (1) the relationship between humans and God in which there is an embodiment of the moral value of praying, there are 3 character quotes, and obedience to God is 3 character quotes. (2) The human relationship with oneself which contains honest moral values ​​is 13 character quotations, 13 character quotations are responsible, 7 character quotations are firm, self-control is 1 character quotation, and 3 character quotations are despicable. (3) Human relations with other humans in which there is a form of moral value caring for others totaling 18 character quotes, respecting others totaling 17 character quotes, please help totaling 3 character quotes, compassion totaling 13 character quotes, advising totaling 9 character quotes, and spread greetings totaling 2 character quotes. In addition, in the analysis of moral values ​​there is relevance to learning literature, namely the Prose Fiction Appreciation Theory course regarding moral elements in fiction in the Indonesian Language and Literature Education Study Program.